Pharmacogenetics of the Cytochromes P450 - Daly, Ann K. (Current Topics in Medicinal Chemistry, 2004)
The cytochromes P450 are a family of heme-containing proteins with a major role in the oxidation of both xenobiotics (including prescribed drugs) and endogenous compounds. There are at least 57 human P450s (termed isoforms) which are all encoded by separate genes but only 10 of these contribute to drug metabolism, with the major contribution coming from only 3 isoforms, CYP3A4, CYP2D6 and CYP2C9. It is now well recognised that most cytochrome P450 genes are subject to genetic polymorphism and that therefore some individuals have sequence changes present that result in the production of an enzyme with altered catalytic activity or give rise to abnormal gene expression. This article describes the range of genetic polymorphisms now known to occur in the drug metabolizing cytochromes P450 with particular reference to their functional effects and the influence of ethnic origin on the frequency of variant alleles. The relevance of the various polymorphisms to drug response and toxicity is considered as well as the possibility that genotype for these polymorphisms may be a determinant for “personalized prescribing” in the future.
Keywords: endogenous compounds